THE EFFECT OF RIVALRY CIBLING WITH SOCIAL ADAPTATION OF CHILDREN 11-12 YEARS OLD - dyah pitaloka; arum cahyani (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
The age of 11-12 years of children is in school age where at this age the influence of peer groups has begun to dominate the child, this makes social development at this age obtained from their interactions with other people at school. The failure of social adaptation in school will have bad consequences such as feeling unhappy and disliking yourself. Social adaptation can be influenced by several factors, one of which is sibling rivalry. The purpose of this study was to determine the relationship between sibling rivalry and the social adaptability of children aged 11-12 years.The research method used was a cross-sectional study approach, the population used was children aged 11-12 years at SDN Sidorejo 1 Tuban who had 35 younger siblings according to the inclusion criteria, with a sample size of 32 respondents who were determined using simple random sampling technique. The independent variable in this study is sibling rivalry, while the dependent variable is social adaptability. The instrument used in data collection was a questionnaire. The research analysis used the phie coefficient test.The results showed that there was an influence between sibling rivalry and social adaptability. This is evidenced by the results of the statistical analysis test, the coefficient of phie α = 0.05, obtained  = 0.000 where  <0.05, then H1 is accepted that there is a relationship between sibling rivalry and social adaptability with a value of (r) = 0.663. Based on the results of this study, schools can pay more attention to helping children make social adaptations, especially for children who experience sibling rivalry.